2006
DOI: 10.1191/0960327106ht612oa
|View full text |Cite
|
Sign up to set email alerts
|

Demographical, aetiological and clinical characteristics of poisonings in Mersin, Turkey

Abstract: Background: As acute poisoning continues to be an important public health problem, and represents a frequent cause of admission in emergency departments, there is a constant need to have up to date information about it. The aim of this retrospective study was to evaluate the demographical, aetiological and clinical characteristics of acute poisonings who were admitted to a university hospital in the south part of Turkey. Methods: The data of 195 acute poisoning patients who were admitted to the Emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
37
0
7

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 25 publications
12
37
0
7
Order By: Relevance
“…According to the results of quite a few epidemiologic studies conducted in our country, the annual poisoning incidence was determined as 0.8-5% (5)(6)(7)(8). So the rate of 1.1% that we found in this study performed at a university hospital in the province of Van, located in the most eastern part of Turkey, is in accordance with the literature findings.…”
Section: Discussionsupporting
confidence: 81%
“…According to the results of quite a few epidemiologic studies conducted in our country, the annual poisoning incidence was determined as 0.8-5% (5)(6)(7)(8). So the rate of 1.1% that we found in this study performed at a university hospital in the province of Van, located in the most eastern part of Turkey, is in accordance with the literature findings.…”
Section: Discussionsupporting
confidence: 81%
“…[4][5][6]17,18 Em relação à idade, notou-se uma variação significante com as intoxicações por medicamentos aumentando com a idade enquanto decresceu a participação dos produtos químicos de uso doméstico. Não existem maiores evidências de que a redução de 8% no número total de casos anuais de intoxicações, reflexo da diminuição em 1/4 das intoxicações por produtos químicos de uso doméstico, possa ser atribuída a qualquer tipo de ação de saúde pública especificamente orientada para tal problema no período estudado.…”
Section: Discussionunclassified
“…In the study of Özayar et al (12), it was reported similarly that antidepressants were in the first order among drug intoxications with a rate of 31.9% and this was followed by analgesics with a rate of 17.02%. When the literature was examined, it was found that analgesics in some studies and antidepressants in some others were in the first order (15)(16)(17)(18)(19)(20)(21). In contrast to these studies, the rate of antibiotic intoxication was also found to be subtantially high in our study.…”
Section: Discussionmentioning
confidence: 99%